Preparation of mesoporous nitrogen-doped titania comprising large crystallites with low thermal conductivity. Issue 11 (18th May 2022) - Shimasaki, Yuta; Matsuno, Takamichi; Guo, Quansheng; Shimojima, Atsushi; Wada, Hiroaki; Mori, Takao; Kuroda, Kazuyuki
Abstract : Highly ordered mesoporous N-doped TiO2 with large crystallites was prepared by hard-templating method, followed by calcination with urea. The thermal conductivity was lowered by the nanosized pore walls and the ordered pore wall surfaces. Abstract : Reducing the thermal conductivity ( κ ) of mesoporous N-doped titania (TiO2 ) is crucial for the development of TiO2 -based materials that exhibit excellent electronic, photochemical, and thermoelectric properties. Mesopores can contribute to the reduction of κ via phonon scattering, and the scattering effect due to the randomness of crystal interfaces should be significantly reduced to clarify the role of mesopores in reducing thermal conductivity. Highly ordered mesoporous N-doped TiO2 comprising large crystallites was prepared with silica colloidal crystals as a template into which a Ti source was introduced, followed by calcination with urea. N-doped samples comprising large crystallites exhibiting random mesopores were also prepared and used for the investigation of the effects of the shape and arrangement of the mesopore on phonon scattering. The mesostructures of the two separately prepared N-doped TiO2 samples were retained after sintering at 873 K and 80 MPa to fabricate pellets. Furthermore, the effective suppression of the long mean-free-path phonon conduction by the thin pore walls at a nanometer scale thickness significantly reduced the thermal conductivities of both samples. The presence of ordered mesopores further contributed to the reduction of κ, which was probably due to the enhanced contribution of the backscattering of phonons caused by ordered pore wall surfaces.